Student Problematics in Islamic Education Learning at High School - Anisah, Indira Dwi; Arsyad, Junaidi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to describe the problem in the PAI learning process at SMAS Imelda Medan. This type of research is descriptive qualitative. The subject of the study includes 30 students who are selected purposefully. Data are collected through observation, interview, and documentation. Data analysis was performed by following the interactive model of Miles and Huberman with several stages, including data collection, data reduction, display data, and conclusion drawing. Based on the interview and the documentation results, the problem happened because of the lack of student learning interest, the lack of students' understanding of PAI learning, many students who have not been smoothly reading the Qur'an, and fewer professional teachers, and less competent teacher, and limited facilities and infrastructure and environmental problems. Solutions that can be done to fix the PAI learning issue at SMAS Imelda Medan include improving teacher professionalism, infrastructure facilities, and media utilization.